Distinct gastric phenotype in patients with pathogenic variants in SMAD4: A nationwide cross-sectional study - Jelsig, Anne Marie; Qvist, Niels; Bertelsen, Birgitte; Christensen, Lise-Lotte; Grossjohan, Hanne; Lautrup, Charlotte Kvist; Sunde, Lone; Tørring, Pernille Mathiesen; Ljungman, Ken; Christensen, Louise Torp; Karstensen, John Gásdal (Endoscopy International Open, 2022)
Background and study aims In most patients with juvenile polyposis Syndrome, it is possible to detect a pathogenic germline variant in SMAD4 or BMPR1A. It is well known that patients with a pathogenic variant in SMAD4 have a higher risk of gastric polyposis and gastric cancer compared to BMPR1A carriers, but the natural history of gastric involvement is poorly described. We aimed to systematically review endoscopic and histopathological gastric findings in Danish patients with pathogenic variants in SMAD4.Patients and methods This was a retrospective, cross-sectional study including endoscopic and histological gastric findings in all known Danish patients with pathogenic variants in SMAD4. The patients were identified by data from various registries as well as from clinical genetic departments and laboratories. Results We identified 41 patients (2–72 years) with a pathogenic SMAD4 variant. In 31 patients, we were able to retrieve information on upper gastrointestinal endoscopy. Eighty-seven percent had at least one gastric abnormality including erythema (72 %) and edema (72 %). Half of the patients also had vulnerability of the mucosa and 68 % had gastric polyposis. An increasing frequency of abnormalities were observed with increasing age. Gastric cancer was diagnosed in 5 % of the cases and 22 % had a gastrectomy mainly because of massive polyposis. Conclusions This study showed that most patients with pathogenic SMAD4 variants have a distinct phenotype of the gastric mucosa, and with an increasing severity in the elderly patients. These findings provide new insights into the natural history of gastric manifestations in patients with pathogenic SMAD4 variants.